Death Sentences for Criminal Acts of Narcotics in a Juridical Review - Taufiqqurrahman Siregar; Sriono Sriono; Bernat Panjaitan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Narcotics crime is an extraordinary crime, also known as extraordinary crime, which can endanger or even kill the lives of others. Therefore, law enforcement must also be done in an extraordinary way so as to provide a deterrent effect to the perpetrators of narcotics crimes. The purpose of this study is to discuss the juridical review of the implementation of the death penalty for narcotics criminals, human rights views on the death penalty for narcotics criminals, as well as the factors that influence judges in deciding the death penalty for narcotics criminals. The research method used is normative legal research by collecting library data. The results of this study are the determination of the death penalty for narcotics criminals who are without rights or against the law to possess, store, control, or provide, produce, import, export, or distribute narcotics and exceed 1 (one) kilogram or exceed 5 kilograms. (five) tree trunks or in the form of non-plants weighing 5 (five) grams are valid and expressly regulated in Chapter XV concerning Criminal Provisions, especially in article 113, article 114, article 116, article 118, article 119, article 121, and Article 133 of Law Number 35 of 2009 concerning Narcotics. Human rights views on the death penalty also cannot be categorized as a violation, because there are other human rights that must be protected from the dangers of narcotics abuse which can endanger the lives of others. Judges in deciding the death penalty have had strong considerations based on the principles of justice, legal certainty and expediency in each of their decisions.